2016
DOI: 10.1590/1413-812320152112.17962015
|View full text |Cite
|
Sign up to set email alerts
|

Intenção materna de amamentar: revisão sistemática

Abstract: Intenção materna de amamentar: revisão sistemática Maternal intention to breastfeed: a systematic reviewResumo O presente estudo tem como objetivo identificar os fatores associados à intenção materna para amamentar (IMA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
1
18
0
10
Order By: Relevance
“…Despite the intention of represent an expectation regarding a future behavior, the results found in this research are consistent with findings from other studies regarding the factors that influence IB [9][10][11]19 , but they present a higher expectation when compared to surveys conducted in the United States (44.9% to 64.6%) 9,11,15,22,23 in England (20.0%) 24 and in China (53.9%) 25 . In addition, the available data of national studies on breastfeeding are of 2008 7 , and studies that have assessed the time trend in the duration of breastfeeding in Brazil have indicated an increase in the total duration and in the prevalence of EB 16,17,26 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Despite the intention of represent an expectation regarding a future behavior, the results found in this research are consistent with findings from other studies regarding the factors that influence IB [9][10][11]19 , but they present a higher expectation when compared to surveys conducted in the United States (44.9% to 64.6%) 9,11,15,22,23 in England (20.0%) 24 and in China (53.9%) 25 . In addition, the available data of national studies on breastfeeding are of 2008 7 , and studies that have assessed the time trend in the duration of breastfeeding in Brazil have indicated an increase in the total duration and in the prevalence of EB 16,17,26 .…”
Section: Discussionsupporting
confidence: 89%
“…In addition to contributing in the total duration of breastfeeding 9 , having a partner can positively influence IB, as uncovered in the present and other studies 15,24,27 . On the one hand, during the breastfeeding period, emotional, social and economic supports emerge as the most important, and the partner stands out and has the greater weight in this period 10,11,[28][29][30] . On the other hand, a retrospective study with women in the military residing in the metropolitan region of Belo Horizonte (MG) demonstrated that, when compared to unmarried women, married women breastfed for less time (OR 7,08 95%CI 1.98; 25.16) 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The qualification criteria will correspond to a scale 29 adapted for this study with a maximum score of 29 points for each article. "Score zero" was considered when the information was not specified in the text, or did not meet the minimum criteria for the classification of quality.…”
Section: Methodsmentioning
confidence: 99%